Kemampuan Berpikir Kritis Matematis Siswa pada Materi Statistika Kelas X SMA Kemala Bhayangkari 1 Medan : Penelitian - Carissa Ghaniya Azzahra; Dedy Juliandri Panjaitan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Critical thinking in mathematics is the ability and disposition to combine knowledge, mathematical reasoning, and cognitive strategies to generalize, prove, or evaluate mathematical situations effectively. This research aims to find out how students' mathematical critical thinking abilities are in statistics material for Class X SMA Kemala Bhayangkari 1 Medan. This type of research is a qualitative descriptive method. This research was carried out at SMA Kemala Bhayangkari 1 Medan. The instruments used were test questions and interviews. The participants in this research were the entire X-Mia 1 class, totaling 21 students. Based on the research results, it can be concluded that students' ability to think critically in statistical material is classified as moderate, each student has a different level of achievement for each indicator. Due to the lack of accuracy in checking and understanding the truth in the statements given in the questions as well as including solutions and errors in indicating more specific parts. This results in errors in calculating and drawing conclusions.